Simulation-based low-dose, high-frequency plus mobile mentoring versus traditional group-based trainings among health workers on day of birth care in Nigeria; a cluster randomized controlled trial - Emmanuel Ugwa; Mark Kabue; Emmanuel Otolorin; Gayane Yenokyan; Adetiloye Oniyire; Bright Orji; Ugo Okoli; Joseph Enne; Gabriel Alobo; Gladys Olisaekee; Adebayo Oluwatobi; Chioma Oduenyi; et al. (BMC, 2020)
Abstract Background The aim of this study was to compare health workers knowledge and skills competencies between those trained using the onsite simulation-based, low-dose, high frequency training plus mobile mentoring (LDHF/m-mentoring) and the ones trained through traditional offsite, group-based training (TRAD) approach in Kogi and Ebonyi states, Nigeria, over a 12-month period. Methods A prospective cluster randomized controlled trial was conducted by enrolling 299 health workers who provided healthcare to mothers and their babies on the day of birth in 60 health facilities in Kogi and Ebonyi states. These were randomized to either LDHF/m-mentoring (intervention, n = 30 facilities) or traditional group-based training (control, n = 30 facilities) control arm. They received Basic Emergency Obstetrics and Newborn Care (BEmONC) training with simulated practice using anatomic models and role-plays. The control arm was trained offsite while the intervention arm was trained onsite where they worked. Mentorship was done through telephone calls and reminder text messages. The multiple choice questions (MCQs) and objective structured clinical examinations (OSCEs) mean scores were compared; p-value < 0.05 was considered statistically significant. Qualitative data were also collected and content analysis was conducted. Results The mean knowledge scores between the two arms at months 3 and 12 post-training were equally high; no statistically significant differences. Both arms showed improvements in composite scores for assessed BEmONC clinical skills from around 30% at baseline to 75% and above at end line (p < 0.05). Overall, the observed improvement and retention of skills was higher in intervention arm compared to the control arm at 12 months post-training, (p < 0.05). Some LDHF/m-mentoring approach trainees reported that mentors' support improved their acquisition and maintenance of knowledge and skills, which may have led to reductions in maternal and newborn deaths in their facilities. Conclusion The LDHF/m-mentoring intervention is more effective than TRAD approach in improving health workers' skills acquisition and retention. Health care managers should have the option to select the LDHF/m-mentoring learning approach, depending on their country's priorities or context, as it ensures health workers remain in their place of work during training events thus less disruption to service delivery. Trial registration The trial was retrospectively registered on August 24, 2017 at ClinicalTrials.Gov: NCT03269240 .